1990
DOI: 10.1093/bja/64.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Depth and Duration of Skin Analgesia to Needle Insertion After Topical Application of Emla Cream

Abstract: We have determined the depth and duration of analgesia to needle insertion after topical application of EMLA cream (Eutectic Mixture of Local Analgesics). EMLA was applied for 30, 60, 90 and 120 min and the sensory and pain threshold depths were determined before analgesia (1.0 and 1.9 mm, respectively) and up to 4 h after the cream was removed from the skin. The maximal depth of analgesia (approx. 5 mm) was observed 30 min after a 90-min application and during the 60-min period after a 120-min application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
129
0
7

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(139 citation statements)
references
References 8 publications
3
129
0
7
Order By: Relevance
“…Previous studies indicate that various contributory factors can affect pain intensity during injection, such as velocity, 39,40 angle of insertion, 39 depth of injection, 41 needle diameter, 39,42 needle tip bluntness, 43 regional variation, 44 and activated nociceptor density. 40 Jorgensen 42 suggested that thinner needles induce less injection pain, but another study that used an automated and controlled needle insertion device found that although needle diameter could affect pain intensity when the skin is repeatedly needled, pain intensity for a single cutaneous needle insertion is not significantly related to needle length or diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicate that various contributory factors can affect pain intensity during injection, such as velocity, 39,40 angle of insertion, 39 depth of injection, 41 needle diameter, 39,42 needle tip bluntness, 43 regional variation, 44 and activated nociceptor density. 40 Jorgensen 42 suggested that thinner needles induce less injection pain, but another study that used an automated and controlled needle insertion device found that although needle diameter could affect pain intensity when the skin is repeatedly needled, pain intensity for a single cutaneous needle insertion is not significantly related to needle length or diameter.…”
Section: Discussionmentioning
confidence: 99%
“…40 Jorgensen 42 suggested that thinner needles induce less injection pain, but another study that used an automated and controlled needle insertion device found that although needle diameter could affect pain intensity when the skin is repeatedly needled, pain intensity for a single cutaneous needle insertion is not significantly related to needle length or diameter. 40 Unlike previous studies, [39][40][41][42][43][44] which investigated the intensity of pain caused by skin damage by single or repeated subcutaneous or intradermal injections, trigger point injections may have different contributing factors because repeated injections to muscle, along with single skin insertion, are the main causes of pain. We considered that LTR originating from muscle and fascia might also contribute to pain during trigger point injection.…”
Section: Discussionmentioning
confidence: 99%
“…10 The maximal depth of analgesia (5 mm) has been observed for 30 min after a 90 min application, and during the 60 min period after a 120 min application. 14 Since EMLA has been reported to provide effective anaesthesia for venepuncture, subcutaneous injection, and even split skin grafting, 10,15 we did not think a controlled trial comparing the efficacy of the EMLA cream against a control group was necessary in this study. Instead, we wanted to ascertain if the use of alkalinized LA solution is necessary in the presence of EMLA.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Eutectic mixture of local analgesics has also been used to alleviate cutaneous pain in children and adults. 4 However, for optimal analgesic effects, the correct amount of the drug must be applied and the skin should be properly dressed for an effective absorption. 4 In this regard, lidocaine tape has advantages and is frequently used because of easier application.…”
Section: Skin Analgesia With Lidocaine Tape Prior To Epidural Blockadementioning
confidence: 99%
“…4 However, for optimal analgesic effects, the correct amount of the drug must be applied and the skin should be properly dressed for an effective absorption. 4 In this regard, lidocaine tape has advantages and is frequently used because of easier application. However, although the tape is clinically useful, elevation of the pain threshold as measured by depth of needle insertion and the optimal duration of application remain unclear.…”
mentioning
confidence: 99%